Strengthening Environmental Responsibility through Ecological Citizenship at the Local Community Level - Sri Rahayu Pudjiastuti (PT FORMOSA CENDEKIA GLOBAL, 2026)
Environmental degradation at the local community level is still an ongoing problem, which shows that a technical approach alone is not enough without strengthening citizens' environmental responsibility. From a civic perspective, ecological citizenship offers a conceptual framework that places environmental concern as an integral part of everyday civic rights, obligations, and practices. This study aims to analyze the role of ecological citizenship in strengthening environmental responsibility at the local community level. The research uses a mixed-methods approach with a sequential explanatory design. Quantitative data was collected through a structured questionnaire of 80 adults in a rural community in West Java, while qualitative data was obtained through in-depth interviews with eight key informants consisting of village officials, community leaders, environmental activists, and residents with varying levels of ecological citizenship. Quantitative data analysis was carried out using descriptive statistics, correlation tests, and simple linear regression, while qualitative data was analyzed through thematic analysis and triangulation. The results of the study show that ecological citizenship has a positive and significant effect on environmental responsibility, especially in encouraging pro-environmental behaviors such as waste management, collective participation, and compliance with local environmental norms. Qualitative findings corroborate that social norms, local leadership, and community-based environmental programs play an important role in actualizing ecological awareness into concrete action. This study concludes that strengthening ecological citizenship at the local community level is a key strategy in building sustainable environmental responsibility and making a practical contribution to the development of citizenship-based environmental governance.